2018
DOI: 10.1007/s11095-017-2325-x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Transformation of Indomethacin during Hot Melt Extrusion Granulation: Process and Dissolution Control

Abstract: By determining the conditions that either prevent or facilitate process induced transformations of IMC polymorphs during melt granulation, a design space was developed to control the polymorph present in the resulting granules. This represents the conditions necessary to balance the thermodynamic relationships between the polymorphs of the IMC system and the kinetics of the possible transformations as a function of the processing stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…From the DSC thermograms, the melting points of IM bulk powder and IM microparticles without PVA were 161 °C and 155 °C, respectively. Previous reports suggested that the IM crystal form, showing a peak at 161 °C, was the γ form, and that the IM crystal form showing a peak at 155 °C was the α form [ 27 , 28 ]. The DSC results were also consistent with the results of the XRPD spectrum and the morphological features [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…From the DSC thermograms, the melting points of IM bulk powder and IM microparticles without PVA were 161 °C and 155 °C, respectively. Previous reports suggested that the IM crystal form, showing a peak at 161 °C, was the γ form, and that the IM crystal form showing a peak at 155 °C was the α form [ 27 , 28 ]. The DSC results were also consistent with the results of the XRPD spectrum and the morphological features [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Crystal data and physical properties of the α and γ polymorphs of indomethacin [8,9,12,[14][15][16]. The interconversion of α-IM to γ-IM, specifically, can occur due to heat, solvent, mechanical action, such as milling, and exposure to the more stable γ form [12,[36][37][38]. This transformation has been reported in several previous studies and it follows Ostwald's rule of phases with the metastable α-form converting to the more stable γ-form [9,39].…”
Section: Introductionmentioning
confidence: 99%
“…The α to γ transition has previously led to limitations in studying α-IM, especially while using thermal analysis techniques [ 7 ]. Interconversion has also caused issues with using α-IM in hot melt extrusion, an emerging technique for downstream API processing [ 37 ]. It has also been suggested that the presence of small amounts of γ-IM can result in the transformation of the α form [ 12 ], indicating that any impurities or γ seeds during production could lead to interconversion and lower the solubility of the final drug products.…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques, such as conventional tablet pressing [ 21 ], freeze-drying [ 22 ], hot-melt extrusion (HME) [ 23 ] and melt-adsorption [ 24 ], are employed for manufacturing ODTs, and HME was utilized in this study. HME has been applied to a wide variety of pharmaceutical dosage forms, including granules [ 25 ], pellets [ 26 ], films [ 27 ], tablets [ 28 ] and implants [ 29 ]. It is widely accepted that HME is easy to scale up and operate continuously as a solvent-free and energy-saving approach for the preparation of various pharmaceutical systems [ 30 ]; moreover, HME can not only enhance the solubility and bioavailability of poorly soluble active pharmaceutical ingredients (APIs), it also improves their stability and bitter taste [ 31 ] and is especially suitable for preparing ODTs.…”
Section: Introductionmentioning
confidence: 99%